2011
DOI: 10.1021/es103080p
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Exposure Close to Air Pollution Sources in Naturally Ventilated Residences: Association of Turbulent Diffusion Coefficient with Air Change Rate

Abstract: For modeling exposure close to an indoor air pollution source, an isotropic turbulent diffusion coefficient is used to represent the average spread of emissions. However, its magnitude indoors has been difficult to assess experimentally due to limitations in the number of monitors available. We used 30-37 real-time monitors to simultaneously measure CO at different angles and distances from a continuous indoor point source. For 11 experiments involving two houses, with natural ventilation conditions ranging fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 35 publications
5
65
0
Order By: Relevance
“…Without loss of generality, we assume constant values for the following parameters during the optimizations: S th = 0.35, Q = 0.01 g/s, k = 10 5 and the environment size is 100 × 100 m 2 . These values are close to real world experimental measurements [47].…”
Section: Optimal Sensor Deploymentsupporting
confidence: 90%
“…Without loss of generality, we assume constant values for the following parameters during the optimizations: S th = 0.35, Q = 0.01 g/s, k = 10 5 and the environment size is 100 × 100 m 2 . These values are close to real world experimental measurements [47].…”
Section: Optimal Sensor Deploymentsupporting
confidence: 90%
“…It is noteworthy that all three non‐smokers experienced significant SHS exposure during each of the five active smoking periods in the garage. This may be due, at least in part, to greater turbulent mixing in this location – it has been found that the turbulent diffusion coefficient indoors increases with the air change rate (Cheng et al., ).…”
Section: Resultsmentioning
confidence: 83%
“…Individuals may open windows and doors when sweeping and dusting, which will increase ACRs; these activities are also likely to entrain dust and thus increase PM concentrations. The Detroit data does not include variables reflecting opened windows and doors, a strong determinant of ACRs as shown in studies in Ohio [11], California and Virginia [8], Redwood City and Watsonville, CA [43], Columbus, OH [11], Odense, Denmark [37], and Boston, MA [41]. As noted earlier, wind speed and indoor-outdoor temperature differentials are important determinants of ACRs [1,8,9,11].…”
Section: Resultsmentioning
confidence: 99%